Peran Citra Merek Memediasi Pengaruh Inovasi Produk dan Digital Marketing terhadap Keputusan Pembelian : Studi pada Kedai “Duduk Makan” di Kota Denpasar - Tristan Omar Farouk; I Putu Gde Sukaatmadja (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the role of brand image in mediating the influence of product innovation and digital marketing on purchasing decisions at the “Duduk Makan” shop. The study refers to the Theory of Planned Behavior (TPB), which explains that product innovation and digital marketing can shape positive consumer attitudes, while brand image acts as a mediator that strengthens the relationship between variables. The phenomenon of fluctuations in the number of consumers and the results of the pre-survey that showed low perceptions of innovation, digital marketing, and brand image are the basis for conducting this study. The research approach used is quantitative, with data collection through questionnaires analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) with the help of SmartPLS 4.1 software. The research respondents numbered 100 people who had made purchases at the “Duduk Makan” shop. The results show that product innovation and digital marketing have a positive effect on brand image and purchasing decisions. Brand image is also proven to have a significant effect on purchasing decisions and mediates the influence of product innovation and digital marketing on purchasing decisions. These findings confirm that relevant innovation, effective digital marketing strategies, and a strong brand image can shape positive consumer attitudes, ultimately driving purchasing decisions in line with the TPB perspective. This research provides both theoretical contributions and practical recommendations for Kedai “Duduk Makan” in designing a more effective marketing strategy.